2020
DOI: 10.1002/adfm.202008901
|View full text |Cite
|
Sign up to set email alerts
|

Robust High‐Temperature Supercapacitors Based on SiC Nanowires

Abstract: Currently, the exploration of energy conversion/storage devices for high‐temperature operation with desired stability is still a grand challenge. In the present work, the high‐temperature supercapacitors (SCs) based on SiC nanowires as the electrode materials are reported, which are synthesized via pyrolysis of polymeric precursors followed by etching for creating more active sites with enhanced surface area. In 2.0 m KCl aqueous electrolyte, the as‐fabricated electrode based on etched SiC nanowires delivers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…The group also assembled an ionic-liquid-based device withstanding a temperature range of 0-150 °C, in which SiC nanowires electrodes were grown via pyrolysis of polymeric precursor, followed by etching technique to maximize surface area. [140] Under current density of 2.5 A g −1 , the areal capacitance varied from 6.05 mF cm −2 (at 0 °C) to 18.5 mF cm −2 (at 150 °C); and after 10 000 cycles, capacitance retentions of around 80% were reported under different temperatures (0, 25, 50, 100, and 150 °C). Remarkably, under continuous heating/cooling between 0 and 150 °C within 12 000 cycles, the capacitance retention still remained higher than 75%.…”
Section: Sic-based Supercapacitors Under High/low Temperaturesmentioning
confidence: 93%
See 2 more Smart Citations
“…The group also assembled an ionic-liquid-based device withstanding a temperature range of 0-150 °C, in which SiC nanowires electrodes were grown via pyrolysis of polymeric precursor, followed by etching technique to maximize surface area. [140] Under current density of 2.5 A g −1 , the areal capacitance varied from 6.05 mF cm −2 (at 0 °C) to 18.5 mF cm −2 (at 150 °C); and after 10 000 cycles, capacitance retentions of around 80% were reported under different temperatures (0, 25, 50, 100, and 150 °C). Remarkably, under continuous heating/cooling between 0 and 150 °C within 12 000 cycles, the capacitance retention still remained higher than 75%.…”
Section: Sic-based Supercapacitors Under High/low Temperaturesmentioning
confidence: 93%
“…First and foremost, morphological optimization of pristine SiC has been extensively studied to maximize specific surface area and facilitate ion and electron transport. Several SiC nanostructures have been investigated, including nanowires, [137][138][139][140][141][142] nanochannel arrays, [143] micro-and mesoporous sphere, [144] nanocauliflowers, [145] and thin films. [146] Remarkably, a study on SiC thin films revealed the relationship between their microstructures (defects, phase composition, crystallinity) and electrochemical behaviors.…”
Section: Overview Of Materials Design In Sic Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of digital communication instruments and wireless electronics, the higher requirements such as the stable performance at higher temperatures are put forward for the electrochemical energy storage device [1–4] . Among energy storage devices, supercapacitors have intrinsically higher power density, faster charging and discharging rates, longer cycle life, and higher safety [5–7] for potential high‐temperature environment applications, such as in military equipment or electric vehicles [8–13] . However, the high‐temperature‐induced self‐discharge behavior would badly lead to a large number of voltage attenuation, leakage current and energy storage loss, [14–16] severely restricting the high‐temperature performance of supercapacitor [17] .…”
Section: Introductionmentioning
confidence: 99%
“…With the expansion of commercial markets for electronic devices and electric vehicles, the requirement of supercapacitors with high power density and high energy density becomes more and more urgent, which, in essence, puts forward a higher demand for synthesis technology of the electrode materials. [1][2][3][4][5][6] Among the typical electrode materials for supercapacitors, such as carbon materials, [7,8] conducting polymers, [9,10] metal More recently, with the assistance of Co 2+ /Ni 2+ etching or Mn 2+ / Ni 2+ deposition, Zhang et al have separately prepared CoO/ NiO-Cu@CuO and NiMn-LDH@CuO/CF heterostructures on Cu foams, which, as a result, both exhibit much enhanced electrochemical performance compared with the single CuO precursors. [29,33] In addition, instead of designing the CuO-based hybrid nanorod arrays as above, one-pot hydrothermal method followed by annealing has also been adopted for the preparation of NiO-CuO hollow particles on Ni foams, which could introduce abundant oxygen vacancies in the hybrids to promote their electronic conductivity and thereby increase the electrochemical capacitance.…”
Section: Introductionmentioning
confidence: 99%